PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, AKUNTABILITAS PUBLIK, DESENTRALISASI, DAN SISTEM PENGENDALIAN INTERN TERHADAP KINERJA MANAJERIAL PEMERINTAH DAERAH (Studi Pada SKPD Kabupaten Kuantan Singingi) - Eka Jas Oktavia Sari; Taufeni Taufik; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to determine the empirical evidence of the effect of budget participation, public accountability, decentralization, and the internal control system of the local government managerial performance. The population in this study is 29 working units Kuantan Singingi District. Samples taken amounted to 87 respondents. The type of data used are primary data to the data collection method using a questionnaire. Data analysis method used in this study is multiple regression with SPSS version 17. Research shows that: 1) budgetary participation influence the managerial performance of local governments with a level of sig(0.015) < (0.05) and tcount (2.491) >ttable (1.98861) then H1is accepted, 2) public accountability affect the managerial performance of local governments with a level of sig (0.038) < (0.05) and tcount (2.110) > ttable (1.98861)) then H2 is accepted, 3) decentralization affect the managerial performance of local governments with a level of sig (0.034) < (0.05) and tcount (2.157) > ttable (1.98861) then H3 is accepted and 4) internal control system effect on managerial performance of local governments with a level sig (0.023) < (0.05) and tcount (2.310) > ttable (1.98861) then H4 is accepted. With a total value of R2 square of 0.530 which means that 53% of independent variables in this study could affect the dependent variable, while the rest of 47% is explained by other variables such as motivation, characteristics of the target budget, organizational commitment, and leadership style.Keywords: Managerial Performance of Local Government, Participation Budgeting, Public Accountability, Decentralization, and Internal Control System